2006
DOI: 10.1007/s10543-006-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

On functionally-fitted Runge–Kutta methods

Abstract: Functionally-fitted methods are generalizations of collocation techniques to integrate an equation exactly if its solution is a linear combination of a chosen set of basis functions. When these basis functions are chosen as the power functions, we recover classical algebraic collocation methods. This paper shows that functionally-fitted methods can be derived with less restrictive conditions than previously stated in the literature, and that other related results can be derived in a much more elegant way. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…We briefly summarize the results given in [6] regarding this aspect. Definition 2.2 (Collocation condition).…”
Section: The Collocation Conditionmentioning
confidence: 97%
See 1 more Smart Citation
“…We briefly summarize the results given in [6] regarding this aspect. Definition 2.2 (Collocation condition).…”
Section: The Collocation Conditionmentioning
confidence: 97%
“…As stated in [6], the practical implication here is that the coefficients of an FRK method based on basis functions that satisfy the collocation condition are uniquely determined almost everywhere on the integration domain. Additionally, it is shown in [8,6] that an s-stage FRK method has a stage order s and a step order at least s and at most 2s.…”
Section: The Collocation Conditionmentioning
confidence: 99%
“…In [5] is introduced numerical integration of differential algebraic systems. The use of Runge -Kutta method to solve non-linear system of differential equations is presented in [3]. When time increase (or other parameter used as a step) is variable, it is appropriate to use modified Runge -Kutta -Nyström method, which is modified for variable step of numerical integration.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are developed to integrate an ODE exactly if the solution of the ODE is a linear combination of some certain basis functions (see, e.g., [2], [7], [8], [12], [13], [14], [17]). For example, trigonometric methods have been developed to solve periodic or nearly periodic problems (see, e.g., [7], [11], [17]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, trigonometric methods have been developed to solve periodic or nearly periodic problems (see, e.g., [7], [11], [17]). Numerical experiments have shown that trigonometrically-fitted methods are superior to classical Runge-Kutta methods for solving ODEs whose solutions are periodic or nearly periodic functions with known frequencies (see, e.g., [8], [11], [12], [13], [14], [16], [17]). …”
Section: Introductionmentioning
confidence: 99%